Do Financial Indicators Drive Market Value of Firms in the Transition Economies? The Russian Case. (August 2016) - Gupta, Jyoti; Bunkanwanicha, Pramuan; Khakimov, Sergey; Spieser, Philippe
This article studies the factors which influence market valuation of Russian listed firms. Several financial metrics and corporate governance indicators are analysed. Emphasis is given to multicollinearity and cause-and-effect relationships between independent variables. Main results show that there is no significant correlation between the fundamental financial indicators and the Tobin's Q. However, state ownership, concentration of capital and size are negatively associated with the firm valuation. The evidence suggests that the costs of government ownership outweigh its benefits. JEL classification: G15, G14, C22, F23